New AIE Emitters from the Unexpected Boron Tribromide/Boron Trichloride‐mediated Cyclization Reaction and Application for Fluorescence Imaging of Lipid Droplets - Yichen Hu; Xin Gao; Junlong Ma; Zhichun Shangguan; Liangliang Chen; Guanxin Zhang; Xi‐Sha Zhang; Cheng Li; Yanbang Li; Deqing Zhang (Aggregate)
ABSTRACT The aberrant behavior of lipid droplets (LDs) is often indicative of cellular dysfunction, which may contribute to the development of a range of diseases, particularly metabolic dysfunction‐associated steatotic liver disease (MASLD) and atherosclerosis (AS). Consequently, there is an urgent need to develop fluorescence probes targeting LDs to monitor the progression of disease. In this study, an unanticipated one‐pot boron tribromide (BBr₃)/boron trichloride (BCl₃)‐promoted cyclization reaction was discovered, yielding a bromo‐/chloro‐substituted triphenylamine (TPA) derivative (TPA‐Br/TPA‐Cl). TPA‐Br was successfully transformed into new TPA‐containing donor‐acceptor (D–A) molecules which show typical aggregation induced emission (AIE) property. Among these new AIE emitters, TPA‐N shows the most promising LDs targeting specificity, lowest toxicity and best photo‐stability. Ex vivo studies further demonstrate that TPA‐N can be used to fluorescence image fatty liver and AS plaque quickly and effectively.